HUBUNGAN ANTARA MOTIVASI KERJA DENGAN PRODUKTIVITAS KERJA KARYAWAN SALON KECANTIKAN DI KECAMATAN PADANG BARAT - Ningsih, Sri; Katin, Yusmar Emmy; Rahmiati, Rahmiati (Journal of Home Economics and Tourism, 2012)
The purpose of this research is to see the motivation, describe a bout the productivity, and to look the relationship between work motivation the productivity of beauty salon employee in west Padang. The population in this research are all of the beauty salon employee in west Padang. The sample of this research is the beauty salon employee who nasnigh credibility, and of the instrument that has been used is quisioner that validitaty and realibility have been reshed. The data is analyzed with statistic descriptive, test of analysis , and test of hypothesis. The result of this research show that: 1) the motivation of the beauty salon employee at west Padang in high criteria, 2) the productivity of the beauty salon employee at west Padang in high criteria, 3) they have siqnificant relationship between work motivation and the productivity of beauty salon employee at west Padang.